Sexual Differences in pERK/ERK due to 17-Beta-Estradiol Treatments - Ferrise, Daniel F. (My University, 2014)
Alzheimer's disease is an important disease, affecting both women and men. One area of study is the effect of 17-beta-Estradiol (E2) on neuroprotection. Females have a sharp increase in Alzheimer's onset following menopause. The purpose of this study was to determine where the cell signaling differences inlay.
Color poster with text, images, and graphs.
Keywords: 17 beta-estradiol; Alzheimer's disease; Neuroprotection--Sex difference; Menopause; Posters